Příprava a charakterizace epoxidových zalévacích hmot modifikovaných nanočásticemi - Lednický, Jiří (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2024)
Tato bakalářská práce se zabývá nanokompozity tvořenými organickou matricí ve formě epoxidové pryskyřice a plnivem TiO2 v krystalografickém uspořádání anatasu s rozměry v řádu desítek nanometrů. Práce je zaměřena na porozumění problematiky nanokompozitů, shrnutí výsledků dalších studií, a především na výrobu a charakterizaci vzorků s nanočásticemi dispergovanými pomocí planetárního mlýnu. Dále byl analyzován vliv použitých nanočástic a disperze v planetárním mlýnu na dielektrické vlastnosti čisté epoxidové pryskyřice.

This bachelor's thesis focuses on nanocomposites composed of an organic matrix in the form of epoxy resin and TiO2 filler in the anatase crystallographic structure with dimensions in the order of tens of nanometers. The work is aimed at understanding the issue of nanocomposites, summarizing the results of other studies, and especially at the production and characterization of samples with nanoparticles dispersed using a planetary mill. Furthermore, the effect of the used nanoparticles and dispersion in the planetary mill on the dielectric properties of pure epoxy resin was analyzed.
Preparation and characterization of epoxy potting resins modified with nanoparticles
Keywords: Nanokompozit; nanočástice; disperze; homogenizace; epoxidová pryskyřice; relativní permitivita; ztrátový činitel; elektrická pevnost; vnitřní rezistivita; planetární mlýn.; Nanocomposite; nanoparticles; dispersion; homogenization; epoxy resin; relative permittivity; loss factor; electrical strength; internal resistivity; planetary mill.